Covid-19 pandemic: all possible effective solutions to eradicate the problem. Cross-sectional analysis of clinical, socioeconomic, political and psychological profiles - Perrotta, Giulio (Archives of Community Medicine and Public Health, 2021)
The present work of analysis and research prepares, starting from the biological, clinical, socio-economic and political analysis, an effective intervention plan to eradicate the pandemic problem and its direct and indirect consequences. Passing through the analysis of the therapies and treatments suggested and recommended in case of Covid-19 symptomatology, it is then suggested an integrative clinical plan according to individual needs, to finally focus on the need for socio-economic-political intervention at the community and international level, with direct and immediate effectiveness, with the preparation of a single world currency valid for the pandemic period, a plan for total homestay functional to prevent the spread of infections and a common clinical protocol, suggesting greater attention to the hypothesis of biological therapy and convalescent plasma, waiting for a monoclonal therapy and/or pharmacological more aware and less negatively impacting on the right to individual health than the gene therapies/vaccines of which we do not know yet the medium and long term effects on human health. We analyze the individual critical issues related to vaccine/gene therapy that at the current state of the science: a) have effectiveness that is still lower than natural immunization and does not provide a lasting coverage over time, if not to the extent of 6-9 months to be repeated virtually annually like seasonal flu vaccines; b) do not provide safe immunization over time concerning potential new reactivations and variants of the virus itself. It is no coincidence that we have seen new positivity in subjects already immunized or with the inoculation carried out; c) do not guarantee certain data concerning individual health, in the medium and long term, as well as we do not know the degree of toxicity of the same; d) does not exempt the citizen from the use of the disposable surgical mask, from the social distancing and the hygienic-sanitary rules provided. Based on the evidence found and waiting to find out the fate of the use of convalescent plasma therapy and/or the effectiveness of monoclonal therapy, the most effective drug therapy appears to be the combination of dexamethasone, hydroxychloroquine, heparin (if the D-dimer is high) or salicylic acid (if the D-dimer is not high and there is a modest thrombotic risk), and azithromycin; desirable, if compatible with the clinical picture, the supplements of vitamins A, B (group), C, D and E, in addition to the use of prebiotic supplements, probiotics, omega 3-6-9, coenzyme q10, flavonoids (such as quercetin), glucosamine and lactoferrin, from the earliest moments of the morbid condition, both in preventive and in management phase of the serious patient, in addition to the necessary oxygen therapy support if the clinical conditions require it.